Identifikasi dan Perbaikan Bisnis Proses dalam Kaitannya dengan Pencapaian Visi Organisasi - Helena Kamil (Universitas Bunda Mulia, 2017)
Organizations make common mistakes when determining its goals, where they only focus on to be done actions. But forgotten the detailed work processes and work systems that can support the achievement of the goals. And when the goal is not achieved, organization make the same mistake again by doing corrective actions. Whereas if we talked about organization’s goals or visions, we should concern on the preventives. Organization business process plays an important role as the basis of all work processes and work systems within the organization itself. This research is discussing the business process improvement in a garment manufacturer located at Cakung, Jakarta. Through interview at the early stage, follow with mapping detailed processes using Porter’s Business Value Chain, which has shown Supply chain and Planning process as the focus area. Continue with using Malcolm Baldrige Criteria for Performance Excellence criteria 6 Process Management as a guide to creating a questionnaire to identify current gap versus organization’s needs. The result shows that the organization needs to further clearly identify the Supply chain and Planning process including the process owner.Keywords: Supply Chain and Planning, Work Process, Value Chain, Malcolm Baldrige